CROSS-CULTURAL METHODOLOGY IN SPORT PSYCHOLOGY: THE VALUE-NORMATIVE APPROACH - Yulia Victorovna Paigunova (Sovremennye Issledovaniâ Socialʹnyh Problem, 2016)
Goal. The article analyzes the phenomenon of sport as a tool for the formation of national and citizenship identity, and at the same time, intercultural integration. Method and methodology. Based on the value-normative approach conducted axiological analysis of sport, aimed at the disclosure of ethnic and cultural grounds, socio-political and socio-psychological factors and mechanisms of development of this multi-faceted phenomenon. Sport is considered in terms of its socio-cultural determination, axiological and semantic content. Results. Features of cultural norms and values influence the development of sport as a specific sphere of social interaction are considered. Analysis of genesis, transformation, modification of sport shows its connection with the changes in the social context of its existence. It is shown that sport can be considered as a tool for the formation of national, citizenship identity, along with its role in the intercultural integration. Application of results. Theoretical conclusions of this paper can provide the basis for researches on the problems of sport axiology and in development of psychology and pedagogy programs of sports activities, as well as in teaching special courses in universities, for example, sport pedagogy, sport psychology, conflict management in sport.